REFORMULASI SISTEM PERENCANAAN PEMBANGUNAN NASIONAL DENGAN MODEL GBHN - Siregar, Mardona (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
One of the results of the amendments to the 1945 Constitution was the lossof the GBHN as the state's guidance or direction in implementing nationaldevelopment. This GBHN disappeared along with changes in the duties of theMPR institution as a consequence of the change in its institutional position fromthe highest state institution to a high state institution. As a replacement for theGBHN, Law no. 25 of 2004 regulates the National Development Planning System,which states that the explanation of the objectives for the formation of theRepublic of Indonesia as contained in the Preamble to the 1945 Constitution, isset out in the form of a RPJP (Long Term Development Plan). The RPJP timescale is 20 years, which is then described in the RPJM (Medium TermDevelopment Plan), namely planning with a 5 year time scale, which contains thevision, mission and development program of the elected president, guided by theRPJP. The problem is when the President is in office His term has expired and anew president has been re-elected, so politically the existence of the lawregarding the National Development planning system can very easily be changedto suit the vision and mission of the elected president.